PELAKSANAAN MANAJEMEN WAKIL KEPALA SEKOLAH BIDANG KESISWAAN DALAM PENINGKATAN PELAYANAN PROSES PEMBELAJARAN (STUDI KASUS DI MTs AL-HIKMAH) - Dedi Artanto; Sulthan Syahril; Syawaludin Siregar (UNISAN JURNAL, 2023)
The purpose of this study was to find out the planning, organizing, implementing, and supervising the management of the vice principal of student affairs in improving the service of the learning process at Mts Al-Hikmah. This research uses descriptive qualitative research. In this study, the researcher acted as a key instrument in addition to other supporting instruments such as interview guides, observation guides and audio and video recording tools. Researchers conducted research at Madrasah Tsanawiyah Al-Hikmah Batanghari, where the subjects or sources of data in this study were field teachers, deputy heads of student affairs and madrasah heads. Data collection techniques in this study were interviews and documentation techniques. The data analysis technique has four stages, namely data collection, data reduction, data presentation and the last is drawing conclusions. The results of the study show that planning regarding student management is prepared on the basis of madrasah capabilities and meets the needs of students and the demands of the times. The organizing process is carried out by providing coaching, guidance and special services as well as responsibility towards students themselves, by monitoring and training activities on empowerment and the potentials of students so that students' goals are achieved and they love their school environment. The implementation process is carried out by carrying out special coaching for students who have special interests and talents.